EFFECT OF WOOD GRAIN ORIENTATION ON THE BENDING AND IMPACT STRENGTH OF CARBON FIBER–BALSA WOOD SANDWICH COMPOSITES WITH A POLYESTER RESIN MATRIX - fajar paundra; Khodrani; Fajar Perdana Nurullah; Kardo Rajagukguk; Eko Pujiyulianto; Sena Maulana (Universitas Negeri Semarang, 2025)
The orientation of wood grains significantly determines the mechanical strength of a sandwich composite material where this study aims to analyze the effect of balsa wood grain orientation variations (0°, 30°, 60°, and 90°) as a core material on flexural and impact strength. The materials used in this research consist of a balsa wood core carbon fiber skins, and a polyester resin matrix, fabricated using the vacuum bagging method. The testing procedures include the three-point bending test referring to the ASTM C393 standard, and the drop weight impact test adhering to ASTM D7136. The experimental data were analyzed to evaluate the mechanical strength and failure characteristics resulting from flexural loading and sudden impact. The results indicate that the straight grain orientation (0°) provides a maximum flexural strength of 22.77 MPa and the best impact resistance compared to other grain directions. This study confirms that balsa wood grain orientation has a significant influence on mechanical strength establishing the straight grain as the most optimal configuration for lightweight structural applications that require weight efficiency and high mechanical performance.